DNA‐Templated Biomimetic Enzyme Sheets on Carbon Nanotubes to Sensitively In Situ Detect Superoxide Anions Released from Cells. (17th July 2014) - Ma, Xiaoqing; Hu, Weihua; Guo, Chunxian; Yu, Ling; Gao, Lixia; Xie, Jiale; Li, Chang Ming
<x xml:space="preserve">Abstract</x> Superoxide anion (O2−) is implicated in a wide variety of biological phenomena and oxidative stress‐related diseases. The electrochemical detection of O2− is very attractive but relies on superoxide dismutase enzymes, thus suffering from high cost and low durability. The advances of nanoscience allows architecting while functionalizing a biomimetic sensing platform in nanoscales for high sensitivity and specificity. In this work, manganous phosphate (Mn3(PO4)2) nanosheets, a biomimetic enzyme, are template‐synthesized with DNA and further assembled on carbon nanotubes (CNTs) to form unique DNA‐Mn3(PO4)2‐CNT nanocomposite sheets, of which the Mn3(PO4)2 sheets efficiently catalyze the dismutation of O2− while CNTs enable fast electron transfer, thus achieving highly sensitive and specific detection of O2− with long‐term stability. The biomimetic O2− sensor is further used to monitor O2−in situ released from mouse cancer cell and normal skin cell under drug stimulation, showing excellent real time quantitative detection capability. This work demonstrates a nanoscale approach to not only synthesize but also design a biomimetic enzyme for comparable performance with the natural enzyme‐based biosensor while rendering much higher durability than the natural one and thus holding a great promise for broad applications in fundamental research, clinic diagnostics and screening for drug therapy effects.